Statistical Analysis of COVID-19 Pandemic Across the Provinces of Iraq - Raghad G. Ali Al-Suhail; Layla Fouad Ali (Iraqi Journal of Science, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic is caused by the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which was first identified in December 2019 in Wuhan, China. The outbreak was declared as a Public Health Emergency of International Concern in January 2020 and a pandemic in March 2020. In this study, a complete statistical analysis for SARS-CoV-2 pandemic in entire Iraq, as well as for each governorate separately, is performed for the first time. The study covers a period that starts from the beginning of the pandemic, in the 24th of February 2020, until the 16th of July 2020. It was clear that, although the average number of the reported infection cases was low during February and March, the average infection rate (R0) was >1 (1.3- 2.1), indicating a high spreading rate. During April, when there was a complete lockdown, there was a slight decrease in the RO when the lockdown was lifted, the RO and the number of new cases started to increase rapidly until the 16th of July, when the average number of new cases for every 6 days reached 2281. The cumulative average number of new cases for every six days since the beginning of the pandemic in Iraq on 16 July was 598.4 ±862.4 (Mean± SD). The higher standard deviation than mean value (SD > mean) for most of the analyzes indicates that the official statistics are not reliable. This may be due to the need to conduct further studies as well as the presence of several cases that were not officially reported. In addition, the overall six-day average RO for entire Iraq was 1.4±0.5, with unstable values after the start of the pandemic and absence of monitoring at any time. On the other hand, this study reflects the variations in average RO, average new cases, average recovery rates, average death rates for every 6 days between the Iraqi provinces. Bagdad reported the highest average number of new cases; Babil and Salah aldin reported the highest RO values (2.8± 7.6, 2.5±7.7, respectively). Erbil and Kurkuk reported the highest average recovery rates (372.3± 1340.8, 158±433%, respectively). Babil and Dhiqar reported the highest average death rates (12.2± 63.3, 10.0± 25.8%, respectively), although Duhock did not record any deaths at the time of the study. The data require the attention of the Ministry of Health and Environment to fill in performance holes, as demonstrated by an out-of-control pandemic in Iraq.